2020
DOI: 10.3390/biom10040542
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Cytosolic Group IVA and Calcium-Independent Group VIA Phospholipase A2s to Adrenic Acid Mobilization in Murine Macrophages

Abstract: Adrenic acid (AA), the 2-carbon elongation product of arachidonic acid, is present at significant levels in membrane phospholipids of mouse peritoneal macrophages. Despite its abundance and structural similarity to arachidonic acid, very little is known about the molecular mechanisms governing adrenic acid mobilization in cells of the innate immune system. This contrasts with the wide availability of data on arachidonic acid mobilization. In this work, we used mass-spectrometry-based lipidomic procedures to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 94 publications
(137 reference statements)
2
21
0
Order By: Relevance
“…While the stages of contact, internalization, and activation of transcriptional programs by native or opsonized antigens are well described, much lesser attention has been given to the phospholipid fatty acid remodeling processes occurring during phagocytosis. In previous work from our laboratory, we demonstrated the involvement of several PLA 2 forms, each acting on distinct phospholipid pools and releasing different fatty acids, during zymosan stimulation of mouse peritoneal macrophages [15][16][17]. In addition, we showed that hydrolysis of ethanolamine-containing phospholipids at the membrane is a key event to support phagocytosis of zymosan and live bacteria by human macrophages [18].…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…While the stages of contact, internalization, and activation of transcriptional programs by native or opsonized antigens are well described, much lesser attention has been given to the phospholipid fatty acid remodeling processes occurring during phagocytosis. In previous work from our laboratory, we demonstrated the involvement of several PLA 2 forms, each acting on distinct phospholipid pools and releasing different fatty acids, during zymosan stimulation of mouse peritoneal macrophages [15][16][17]. In addition, we showed that hydrolysis of ethanolamine-containing phospholipids at the membrane is a key event to support phagocytosis of zymosan and live bacteria by human macrophages [18].…”
Section: Introductionmentioning
confidence: 66%
“…This was carried out exactly as described elsewhere [15][16][17][18][19][20][44][45][46][47][48], using a high-performance liquid chromatograph equipped with a binary pump Hitachi LaChrom Elite L-2130 and a Hitachi Autosampler L-2200 (Merck, Madrid. Spain), coupled online to a Bruker Esquire 6000 ion-trap mass spectrometer (Bruker Daltonics, Bremen, Germany).…”
Section: Liquid Chromatography/mass Spectrometry (Lc/ms) Analyses Of mentioning
confidence: 99%
“…In our investigations of obese and non-obese NAFLD/NASH, global deletion iPLA 2 β-null mice were used. Thus, we could not identify whether the observed effects of iPLA 2 β inactivation were due to altered functions in adipocytes [99], immune cells such as macrophages [128,129], and Kupffer cells [130], as well as hepatocytes as shown by our work [39][40][41]. Concurrently, we have also reported that global deletion of iPLA 2 β was able to sensitize hepatocellular damage induced by concanavalin A [131] or during ageing [132].…”
Section: Consideration Of Cell-type Specificity Of Ipla 2 βmentioning
confidence: 63%
“…The effects of iPLA 2 β inactivation in macrophages have been reported [128,129]. On one hand, macrophages from iPLA 2 β-null mice exhibited suppressed pro-inflammatory M1 response [128,130] and showed enhanced IL-4-induced M2 polarization in vitro [128].…”
Section: Consideration Of Cell-type Specificity Of Ipla 2 βmentioning
confidence: 99%
“…iPLA 2 β is in fact involved in regulating several fundamental aspects of monocyte/macrophage biology in addition to those discussed above, including the remodeling the fatty acid composition of macrophage phospholipids [ 94 , 95 ], selection of macrophage phospholipid pools from which to mobilize fatty acids upon cellular stimulation [ 27 , 96 , 97 ], governing the proliferation state of macrophage precursor cells [ 97 ], regulating macrophage apoptosis in the context of lipid stress [ 98 ], regulating the rate of transcription of the macrophage inducible nitric oxide synthase (iNOS) gene [ 26 ], and promoting macrophage adhesion and spreading in response to the engagement of the class A scavenger receptor [ 99 ]. Development of the monocyte/macrophage-selective conditional iPLA 2 β-knockout mice described here may prove to be useful in further characterizing these aspects of monocyte/macrophage biology in models of diabetes, atherosclerosis, and other pathophysiologic states.…”
Section: Discussionmentioning
confidence: 99%